Antibiotic Resistance in Patients with Infective Endocarditis - Hanna B. Koltunova; Kostiantyn P. Chyzh; Olena V. Rudenko; Mikhailo Yu. Antomonov (Ukrainian Journal of Cardiovascular Surgery, 2025)
The incidence of infective endocarditis (IE) is estimated at 3-7/100,000 cases. In international studies, infection was one of the most frequent provoking factors of acute heart failure, recorded in 18.7% of cases in patients with infective endocarditis. Due to the associated high morbidity and mortality, the prescription of appropriate antibiotic therapy and the study of antibiotic resistance remain the focus of research.Аim. To analyze the dynamics of antibiotic resistance in patients with infective endocarditis.Materials and methods. The study included clinical data from 150 patients undergoing cardiopulmonary bypass surgery for active IE from 01.01.2019 to 01.07.2020. Upon hospitalization, patients underwent diagnostic blood cultures with subsequent microbiological identification and antibacterial resistance.Results. Among the positive results of bacteriological blood tests in the group of patients with IE, the frequency of gram-positive flora was 22% of cases, gram-negative flora was detected in 1.3% of cases. The rate of daptomycin-resistant strains was 42.9% in the group of patients without signs of acute heart failure (AHF) and 20.0% in the group with AHF. The level of antimicrobial resistance to linezolid was 40% in the group of patients with IE complicated by AHF and 14.3% in the group of patients without clinical manifestations of AHF at the stage of hospitalisation.Conclusions. Our study revealed a high level of antibiotic resistance in patients with infective endocarditis. In particular, the analysis of antimicrobial resistance to amikacin showed 76.9% in the group of patients without clinical manifestations of acute heart failure. The proportion of strains resistant to daptomycin and teicoplanin was 42.9% and 40.5%, respectively. At the same time, the level of resistance to imipenem was relatively low-12.5% in the group without clinical manifestations of AHF. Effective treatment of infective endocarditis should be based on a combination of early cardiac surgery and rational etiotropic antibiotic therapy, taking into account current data on antibiotic resistance.